Next‐generation agents for fluorescence‐guided glioblastoma surgery - Cristina Chirizzi; Serena Pellegatta; Alessandro Gori; Jacopo Falco; Emanuele Rubiu; Francesco Acerbi; Francesca Baldelli Bombelli (Wiley, 2024)
Abstract Glioblastoma is a fast‐growing and aggressive form of brain cancer. Even with maximal treatment, patients show a low median survival and are often subjected to a high recurrence incidence. The currently available treatments require multimodal management, including maximal safe surgical resection, followed by radiation and chemotherapy. Because of the infiltrative glioblastoma nature, intraoperative differentiation of cancer tissue from normal brain parenchyma is very challenging, and this accounts for the low rate of complete tumor resection. For these reasons, clinicians have increasingly used various intraoperative adjuncts to improve surgical results, such as fluorescent agents. However, most of the existing fluorophores show several limitations such as poor selectivity, photostability, photosensitization and high costs. This could limit their application to successfully improve glioblastoma resection. In the present perspective, we highlight the possibility to develop next‐generation fluorescent tools able to more selectively label cancer cells during surgical resection.